A rare intraosseous schwannoma in the maxillary left incisor region: A case report. Issue 2 (March 2020) - Matsuoka, Yuichiro; Iwamoto, Asuka; Yoshida, Ryoji; Kojima, Taku; Hirayama, Masatoshi; Takahashi, Nozomu; Nakamoto, Masafumi; Nakayama, Hideki
Abstract: A schwannoma is a benign tumor arising from the Schwann cells of the neural sheath. An oral schwannoma is relatively rare. Moreover, an intraosseous schwannoma of the maxilla is extremely rare. Here, we report a schwannoma in the left incisor region of the maxilla. A 61-year-old male was referred to our hospital because of a painless swelling on the left incisor region of the maxilla. A computed tomography scan of the region showed bone resorption, and magnetic resonance images showed a well-defined, circumscribed lesion that was homogeneously hyperintense on T2-weighted images. The lesion was surgically resected after obtaining a definitive diagnosis by biopsy. Histopathological examination of the resected tumor using S-100 protein in an immunohistochemical staining revealed a schwannoma. At 21 months after the surgery, there is no evidence of recurrence or metastasis. To the best of our knowledge, here, we report a rare case of an intraosseous schwannoma of the maxilla. Clinicians, including oral surgeons, should use this study to better understand the clinical, radiological, and histological characteristics of schwannomas.